2018
DOI: 10.33225/pec/18.76.333
|View full text |Cite
|
Sign up to set email alerts
|

Engaging With Edmodo to Teach English Writing of Narrative Texts to Efl Students

Abstract: This experimental research aimed to explore the effect of teaching English writing of narrative texts by using Edmodo learning media through blended learning on the tenth-grade students in one of the senior high schools in Banda Aceh, Indonesia. It further looks into the students’ responses on the use of this media in learning English writing of narrative text. To study the development of the students’ writing before and after using Edmodo learning media in the classroom, the writing tests were given to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 15 publications
0
30
0
4
Order By: Relevance
“…A number of previous studies have concentrated on the effectiveness, effects, and benefits of blended learning using varying designs, scopes, and participants (e.g. Abdul Rahman et al, 2020;Alrouji, 2020;Annamalai, Tan, & Abdullah, 2016;Anggrawan, 2020;Camalahan & Ruley, 2014;Jin, Su, & Lei, 2020;Lam, Hew, & Chiu, 2017;Lien, 2015;McCall, 2017;Milad, 2017;Permana & Santosa, 2018;Permanda, 2017;Scott, Ulmer-Krol, & Jason, 2020;Spanou & Zafiri, 2019;Yusuf, Yusuf, Erdiana, & Pratama, 2018). These studies proved that blended learning is significantly effective in developing positive learning outcomes among ESL students.…”
Section: Blended Learning In the Esl Writing Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of previous studies have concentrated on the effectiveness, effects, and benefits of blended learning using varying designs, scopes, and participants (e.g. Abdul Rahman et al, 2020;Alrouji, 2020;Annamalai, Tan, & Abdullah, 2016;Anggrawan, 2020;Camalahan & Ruley, 2014;Jin, Su, & Lei, 2020;Lam, Hew, & Chiu, 2017;Lien, 2015;McCall, 2017;Milad, 2017;Permana & Santosa, 2018;Permanda, 2017;Scott, Ulmer-Krol, & Jason, 2020;Spanou & Zafiri, 2019;Yusuf, Yusuf, Erdiana, & Pratama, 2018). These studies proved that blended learning is significantly effective in developing positive learning outcomes among ESL students.…”
Section: Blended Learning In the Esl Writing Contextmentioning
confidence: 99%
“…In essence, previous studies found that students' writing performance had improved significantly after learning through the blended learning approach (Annamalai et al, 2016;Camalahan & Ruley, 2014;Jin et al, 2020;Lam et al, 2017;Lien, 2015;Milad, 2017;Permana & Santosa, 2018;Scott et al, 2020). Blended learning was found to improve ESL learners' writing ability, essay composition, critical arguments, linguistic competencies, grammar, spelling, topic sentence, punctuation marks, capitalization, organization, planning as well as reduce language anxiety and outline ideas (Adas & Bakir, 2013;Challob, Bakar, & Latif, 2016;Lam et al, 2017;Permana & Santosa, 2018;Spanou & Zafiri, 2019;Yusuf et al, 2018).…”
Section: Blended Learning In the Esl Writing Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with a widespread broadband internet connection, these factors have affected language learners' learning styles and teaching methods in environments where these mobile technologies are used. A lot of work has been dedicated to explaining how mobile technology can help both conventional and creative ways of teaching and learning, demonstrating how mobile learning can be extended across a broad spectrum of learning activities (Borba et al, 2016;Langbeheim & Levy, 2019;Vu & Thu, 2015;Yusuf et al, 2018) and highlighting the emerging issues. In recent years, there have been many pieces of research exploring the effectiveness of mobile-assisted language learning (MALL) in different contexts, for instance, using mobile phones to deliver physical education course materials (Huy et al, 2020;Vu, 2016a), and using VR materials to support students' practice in badminton sessions.…”
Section: Behavioural Treatments and Token Economymentioning
confidence: 99%
“…Similarly, Suzila et al (2018) employed WhatsApp application as a familiar platform to minimise distractions from mediamorphic elements in blended learning. Yusuf et al (2018) claimed that senior high school students' writing of narrative texts showed improvement with the use of Edmodo, yet the findings were obtained from a simple open-ended questionnaire which may report perceived output rather than actual academic performance. In addition, the research limitation is the validity of the collected comments by students in Edmodo may not abide to pre/post-test conventions.…”
Section: English Language Teaching (Elt)mentioning
confidence: 99%